Management of Volleyball Extracurricular Sports Coaching at High School - Sahabuddin Sahabuddin; H Herman; Nur Windiana (Indonesian Journal of Sport Management, 2023)
The purpose of this study is to ascertain how volleyball extracurricular sports coaching is managed at SMK Negeri 5 Makassar. This study, which is of the descriptive variety, included a total of 20 participants in volleyball extracurriculars as its population. Using SPSS Version 22.00, the descriptive analysis technique, validity, and reliability of the data were examined. Based on the results of the study, the criteria for the management of volleyball extracurricular sports at SMKN 5 Makassar were obtained, including 1 (5%) with very high criteria, 8 (40%) with high criteria, 5 (25%) with very high criteria for medium, and as many as 6 (30%) with a low category. The average value of 27.45 lies in the 75–83 interval, and the highest frequency is also found in the 75–83 interval at 40%, so the management of volleyball extracurricular sports development at SMKN 5 Makassar as a whole gets the high category.